ANALISIS PENDAPATAN USAHATANI KOPI ARABIKA DI DESA COLOL KECAMATAN POCO RANAKA TIMUR KABUPATEN MANGGARAI TIMUR - Felisia Murnilayati; Maria Bano; Kudji Herewila (Undana Press, 2020)
ABSTRACT This research was conducted at Colol Village East Poco Ranaka Sub-District East Manggarai District on March 2019. This research aimed to know: (1) The income bigness of arabica coffee cultivation; (2) The properness of arabica coffee cultivation; (3) the management of arabica coffee cultivation. Data collection method which used in this research was survey method. The determination of research location was purposive sampling with the consideration that Colol Village as one of coffee production village. Kind of data which collected are primary and secondary data. Data were tabulated and analysis as qualitative and quantitative. Income analysis I=TR˗TC used to answer the first aim, and R/C ratio analysis used to answer the second aim. The result of research show that (1) the bigness income of arabica coffee cultivation at Colol Village East Poco Ranaka Sub-District East Manggarai District was high grouped. Total of income as big as Rp.1.503.193.326 with average of Rp.18.110.769 per respondent and average of income per Ha as big as Rp.17.493.593. (2) the bignes of relative profit of arabica coffee cultivation at Colol Village East Poco Ranaka Sub-District East Manggarai District namely 20,00. This case idicated that for every Rp.1 cost which purcased by farmer will obtain revenue as big as 20,00 as profit of arabica coffee cultivation. (3) the power of famer in arabica coffee cultivation was not proper with planing which had decided.